World heritage and tourism : marketing and management - Adie, Bailey Ashton (New York : Routledge, 2019)
This book provides a comprehensive discussion of the phenomenon of World Heritage tourism through a critical, global perspective that encompasses both supply and demand. Individual chapters critically engage with four main topics crucial to this subject area. A chapter on visitors defines the World Heritage tourist segment, highlighting on-site behavior and visitor needs. Building on this, a marketing chapter questions the functionality of the World Heritage brand as a tourist attractor and instead argues that tourist growth is due to effective marketing following World Heritage inscription. The third chapter presents a holistic management framework centred on planning, place, and people, while the concluding chapter situates World Heritage tourism in a global context, discussing threats such as climate change. International case studies from a wide variety of both natural and cultural sites provide a representative discussion of the topic across varying geographical, political, and cultural contexts. This will be of great interest to upper-level students, researchers, and academics in the fields of tourism, heritage studies, and geography, as well as practitioners in these fields who wish to better understand the crucial interplay of these areas.
OCLC-licensed vendor bibliographic record.
Keywords: Heritage tourism -- Management; Hospitality industry -- Management; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism